Improvement and automation of a real-time PCR assay for vaginal fluids. (May 2016) - De Vittori, E.; Giampaoli, S.; Barni, F.; Baldi, M.; Berti, A.; Ripani, L.; Romano Spica, V.
Highlights: An adaptation of the mfDNA extraction protocol to automated platforms is described. The mfDNA obtained through the automated platform allows bacterial identification. An improvement of the ForFLUID kit is presented. Abstract: The identification of vaginal fluids is crucial in forensic science. Several molecular protocols based on PCR amplification of mfDNA (microflora DNA) specific for vaginal bacteria are now available. Unfortunately mfDNA extraction and PCR reactions require manual optimization of several steps. The aim of present study was the verification of a partial automatization of vaginal fluids identification through two instruments widely diffused in forensic laboratories: EZ1 Advanced robot and Rotor Gene Q 5Plex HRM. Moreover, taking advantage of 5-plex thermocycler technology, the ForFluid kit performances were improved by expanding the mfDNA characterization panel with a new bacterial target for vaginal fluids and with an internal positive control (IPC) to monitor PCR inhibition. Results underlined the feasibility of a semi-automated extraction of mfDNA using a BioRobot and demonstrated the analytical improvements of the kit.